(untitled) (International Journal of Innovative Computing, 2024)
This In today’s digital era, individuals are seamlessly connected across various digital platforms, from social media giants like Facebook, Twitter, and Instagram to knowledge-sharing hubs like StackOverflow and Quora. The relentless advancement of digital technologies has ushered in a wave of unprecedented accessibility and connectivity. While this transformation has brought tremendous benefits to society, organizations face new and intricate challenges in adapting to evolving task preferences, performance expectations, and operational requirements. In response to this dynamic landscape, this paper proposes an innovative paradigm shift aimed at enhancing quality, efficiency, and time-to-completion for critical tasks. Central to this transformation is the concept of digitizing manual processes, which offers a transformative approach capable of significantly reducing task durations while ensuring heightened efficiency and minimizing associated risks. One illustrative example involves the automation of employee attendance tracking within a company, seamlessly integrating data into a centralized database. This digitized process not only expedites task completion but also facilitates the generation of detailed reports presented graphically, allowing human resource managers to make informed decisions swiftly. This is just one instance where digitalization outperforms traditional manual methods, leading us to conclude that digitalization is a pivotal strategy for boosting organizational productivity. Moreover, traditional practices in managing meetings, characterized by manual participant notifications, have presented substantial inefficiencies. Secretaries often bear the brunt of coordinating meeting schedules, making phone calls, and sending emails to ensure all involved parties possess accurate information. This paper embarks on a comprehensive investigation to ameliorate this situation by injecting a digitalization approach into the existing meeting management system.